Responsiveness and minimal important differences of common disability measures in people with depression and anxiety disorders - Abdin, Edimansyah; Seet, Vanessa; Jeyagurunathan, Anitha; Tan, Sing Chik; Mohmad Khalid, Muhammad Iskandar Shah; Mok, Yee Ming; Verma, Swapna Kamal; Subramaniam, Mythily (Frontiers in Rehabilitation Sciences, 2025)
BackgroundThe Sheehan Disability Scale (SDS), World Health Organization Disability Assessment Schedule 2.0 12-item version (WHODAS 2.0), and Social and Occupational Functioning Assessment Scale (SOFAS) are commonly used disability measures in patients with depression and anxiety disorders. The current study aimed to compare the responsiveness of these three disability measures and establish their minimal important differences (MID) in the same population.MethodsA total of 308 patients (M = 36.1, SD = 12.7) who were recruited from outpatient clinics and completed all measures at the two assessment points were included in the current study. The MID was estimated using a triangulation approach while the internal and external responsiveness was evaluated using standardized response mean and receiver operating characteristic curves, respectively.ResultsThe best MID estimates for the WHODAS, SDS, and SOFAS were three, four, and six points, respectively. The internal responsiveness analysis showed that all three disability measures were well responsive in patients with improved or stable Patient Health Questionnaire-8 and Generalized Anxiety Disorder-7 scores at the 6-month follow-up. Meanwhile, the external responsiveness analysis demonstrated that all three disability measures showed adequate responsiveness to improvement, with AUC values of at least 0.7. However, when improvement criteria incorporated MID, only WHODAS was found to be adequately responsive.ConclusionThe results of this study will be a helpful guide for clinicians to track and detect meaningful improvements in patient functioning, ensuring continued high-quality clinical care and management.